Microsoft Visual Basic 2013 step by step - Halvorson, Michael (Step by step (Redmond, Wash.), 2013)
Expand your expertise - and teach yourself the fundamentals of Microsoft Visual Basic 2013. If you have previous programming experience but are new to Visual Basic 2013, this tutorial delivers the step-by-step guidance and coding exercises you need to master core topics and techniques.